An integrated spatial snap-shot monitoring method for identifying seasonal changes and spatial changes in surface water quality - Viswanathan, Vidhya Chittoor; Jiang, Yongjun; Berg, Michael; Hunkeler, Daniel; Schirmer, Mario (My University, 2016)
Integrated catchment-scale management approaches in large catchments are often hindered due to the poor understanding of the spatially and seasonally variable pathways of pollutants. High-frequency monitoring of water quality at random locations in a catchment is resource intensive and challenging. A simplified catchment-scale monitoring approach is developed in this study, for the preliminary identification of water quality changes – Integrated spatial snap-shot monitoring (ISSM). This multi-parameter monitoring approach is applied using the isotopes of water (δ18O-H2O and δD) and nitrate (δ15N-NO3− and δ18O-NO3−) together with the fluxes of nitrate and other solutes, which are used as chemical markers. This method involves selection of few sampling stations, which are identified as the hotspots of water quality changes within the catchment. The study was conducted in the peri-alpine Thur catchment in Switzerland, with two snap-shot campaigns (representative of two widely varying hydrological conditions), in summer 2012 (low flow) and spring 2013 (high flow). Significant spatial (varying with elevation) and seasonal changes in the sources of water were observed between the two seasons. A spatial variation of the sources of nitrate and the solute loads was observed, in tandem with the land use changes in the Thur catchment. There is a seasonal shift in the sources of nitrate, it varies from a strong treated waste water signature during the low flow season to a mixture of other sources (like soil nitrogen derived from agriculture), in the high flow season. This demonstrates the influence of other sources that override the influence of waste water treatment plants (WWTPs) during high flow in the Thur River and its tributaries. This method is expected to be a cost-effective alternative, providing snap-shots, that can help in the preliminary identification of the pathways of solutes and their seasonal/spatial changes in catchments.
Keywords: Catchment monitoring; method; Nitrate isotopes; Water isotopes; Nutrient loads; River; Water quality